Pasir Vulkanik sebagai Media Filtrasi dalam Pengolahan Air Bersih Sederhana untuk Menurunkan Kandungan Besi (Fe), Mangan (Mn) dan Kekeruhan Air Sumur Gali - Silviana Dwi Kurniawati; Herman Santjoko; Achmad Husein (Sanitasi: Jurnal Kesehatan Lingkungan, 2017)
Water is the principal component for living things. People of Bantul Krajan Village of Bantul Re-gency use water well as the main source of clean water supply. Problems that often faced by them is the high levels of iron and manganese in the water that decrease the physical quality, because of turbidity, and putrid smells. The purpose of this research was to know the reduction of iron (Fe), manganese (Mn) concentration and turbidity in the dug well water by applying simple water treatment by the benefit of volcanic sand as media filtration This research was an expe-riment with pre-test post-test with control group design in five repetitions. The data were analysed descriptively, and analytically by using the paired t-test of SPSS 16.0 for Windows at 5 % level of significance. The results show that the simple water treatment is able to reduce Fe as much as 1,34 mg/l, Mn of 0,6 mg/l and turbidity of 11,51 NTU, and based on statistical test those reduct-ions are significant (the corresponding p-values are < 0,05). Therefore, it is known that to remove iron, manganese and turbidity in the form of organic and colloid compounds, a simple water treat-ment, i.e. coagulation which is followed by filtration process using volcanic sand as the medium, because it is porous, easy to get and cheap, can be implemented.